Extraction of Gasohol Grade Ethanol from Aqueous Solution using Gasoline as Solvent (Bangladesh Journal of Scientific and Industrial Research, 2008)
Liquid-liquid phase equilibria of ethanol - water - gasoline (iso-octane, octane petrol, kerosene and diesel) were experimentally determined and the ternary phase diagrams of the systems were studied with an end in view to develop methods of producing gasohol by a once through operation. Binodal curves of the different systems were, therefore, obtained to give quantitative ideas about the extent of extraction of alcohol from aqueous solution using gasoline. Phase equilibrium data, distribution coefficient and separation factor were obtained experimentally for ethanolwater- gasoline systems. The order of the heterogeneous region of the solvents is isooctane .octane .petrol < kerosene < diesel. The equilibriation and settling time for ethanol - water - solvent systems are about 10 and 20 min, respectively. The solubility of ethanol in the solvents is in the order of iso-octane .octane.petrol > kerosene> diesel. The distribution coefficient increases with increasing ethanol concentration in the feed; however, to the contrary the separation factor decreases. The distribution co-efficients are lower than 1 and the separation factors are greater than 10 for all of the solvents. Key words: Gasohol, solvent, solvent extraction, gasoline and liquid-liquid equilibria. Bangladesh J. Sci. Ind. Res. 42(3), 287-298, 2007